Chlorella saccharophila cytochrome f and its involvement in the heat shock response - Zuppini, Anna (Journal of experimental botany, 2009)
Cytochrome f is an essential component of the major redox complex of the thylakoid membrane. Cloning and characterization are presented here of a novel partial cDNA (ChspetA) encoding cytochrome f in the psychrophile unicellular green alga Chlorella saccharophila and its involvement in the heat shock (HS) response pathway has been analysed. Semi-quantitative reverse transcriptase PCR analysis showed that ChspetA expression is up-regulated in heat-shocked cells and the protein profile of cytochrome f highlighted a release of cytochrome f into the cytosol depending on the time lapse from the HS. Evans Blue assay, analysis of chromatin condensation, and chloroplast alterations showed the induction of cell death in cell suspensions treated with cytosolic extracts from heat-shocked cells. This study identifies cytochrome f in C. saccharophila that seems to be involved in the HS-induced programmed cell death process. The data suggest that cytochrome f fulfils its role through a modulation of its transcription and translation levels, together with its intracellular localization. This work focuses on a possible role of cytochrome f into the programmed cell death-like process in a unicellular chlorophyte and suggests the existence of chloroplast-mediated programmed cell death machinery in an organism belonging to one of the primary lineages of photosynthetic eukaryotes